FORMULASI SEDIAAN LILIN AROMATERAPI DARI MINYAK ATSIRI DAUN PINUS (Pinus merkusii) - Hutauruk, Dumartina; Sitorus, Binsar; N Daely, Ruth Christiani (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2020)
Aroma therapy is a way of treating the body and healing diseases using essential oils, There are many plants that can produce aroma terapi, one of which is pine. Pine leaves that are processed into essential oils (essential oils) can be used for aroma therapy. Because, this leaf has a aroma that is considered to calm and refresh the mind. The purpose of this study was to prove that pine leaf essential oil can be formulated as aroma therapy wax. The sample used is fresh pine leaves extracted using the water vapor distillation method, then carried out the formulation stage which is then continued with the evaluation stage of aromatherapy wax preparations, namely organoleptic test, burn time test, melting point test, and preference test for panelists. Based on the results of research showing pine leaf essential oil can be formulated into therapeutic aroma wax preparations, the best concentration obtained from F1 is pine leaf essential oil with a concentration of 2%, because the physical form that meets SNI, longer burn time, with a higher melting point and preferred by panelists compared to F2, All wax preparation formulas aromatherapy pine leaf essential oil meets Indonesian national standards (SNI).